Investigating the Role of Viral Hepatitis in the Development of Hepatocellular Carcinoma and the Dependence of Pathogenesis on Viral Hepatitis Types - Toshpulatova, L. (KLINIK VA FUNDAMENTAL TIBBIYOT TADQIQOTLARI JURNALI, 2026)
Viral hepatotropic infections remain the predominant drivers of hepatic oncogenesis globally, dictating diverse molecular pathways that fundamentally alter the clinical presentation and progression of hepatocellular carcinoma. This retrospective cohort study evaluates the specific oncogenic impact, latency periods, and morphological tumor characteristics associated with Hepatitis B, Hepatitis C, and Hepatitis D viral infections. By analyzing a strictly defined cohort of 486 patients diagnosed with primary liver malignancy between 2018 and 2024, the investigation quantifies the distinct evolutionary timelines from chronic viral persistence to malignant transformation. Clinical data, including viral load, fibrotic staging via transient elastography, multiphasic computed tomography morphometrics, and serum alpha-fetoprotein concentrations, were synthesized using multivariate regression models. The analysis revealed profound etiological divergence in oncogenic latency. Patients with chronic Hepatitis C virus exhibited a delayed age of tumor onset (63.4 ± 5.8 years) but demonstrated an accelerated transition from established cirrhosis to carcinoma (4.2 ± 1.1 years). Conversely, Hepatitis B virus cohorts presented with malignancies nearly a decade earlier (54.1 ± 6.2 years), frequently bypassing the intermediate cirrhotic phase entirely due to direct viral DNA genomic integration. The most aggressive oncogenic phenotype emerged within the Hepatitis Delta virus superinfection subgroup, which registered the highest rates of multifocal lesions and early macrovascular invasion. These findings dictate an immediate shift away from universal screening paradigms. Recognizing the virus-specific phenotypic expressions of hepatocellular carcinoma mandates the deployment of tailored, pathogen-specific surveillance protocols, directly improving early detection metrics and expanding the temporal window for curative surgical or ablative interventions.